Making a commitment to ethics in global health research partnerships: a practical tool to support ethical practice - Murphy, Jill; Margaret Hatfield, Jennifer; Afsana, Kaosar; Neufeld, Vic (© 2015 Kluwer Academic Publishers, 2017)
This article was published in Journal of Bioethical Inquiry [© 2015 Kluwer Academic Publishers] and the definite version is available at: http://link.springer.com/article/10.1007/s11673-014-9604-6